Adherence to malaria treatment during pregnancy: does availability and utilization of medical facilities translate to compliance? (2014)
Malaria is a major health issue in sub-Saharan Africa with pregnant women and children at greater risk of exposure to the disease than other population cohorts. Studies on malaria related maternal mortality in Nigeria have focused largely on preventive behaviour and healthcare providers’ knowledge of treatment regimen. Negligible attention has been paid to adherence of care seekers to treatment in relevant contexts. Employing the cross-sectional survey method, 927 pregnant women in Ondo state, Southwest Nigeria were selected through a multistage sampling technique. In addition, 12 In-depth Interviews (IDIs) were conducted among relevant stakeholders. Results showed that adherence to malaria treatment among pregnant women was influenced by social, residential and demographic factors in both rural and urban areas of the state. Expectant mothers without formal education reported higher level of adherence to medication (r=-631 p< .034) than those of higher educational status, indicating that the level of education does not necessarily influence adherence to medication. Policy and national programmes aimed at maternal mortality reduction should recognise the important role that culture plays in people’s perception and behaviour and by implication aetiology of diseases. Without a feasible, people-oriented and context specific intervention, malaria induced maternal morbidity and mortality will remain high not only in Ondo State but Nigeria in general.